1989
DOI: 10.1177/000456328902600605
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Osteocalcin after Femoral Neck Fracture

Abstract: SUMMARY.In a group ofelderly patients with osteoporosis and femoral neck fracture, osteocalcin concentrations rose significantly in the first week after fracture fixation. The changes in osteocalcin correlated well with the changes in plasma 1,25-dihydroxycholecalciferol (P < 0'001).Osteomalacia is an important':" but uncommon] treatable accompaniment of femoral neck fracture. Current biochemical screening tests which rely on measurements of serum calcium and alkaline phosphatase have a high false positive rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 22 publications
1
9
1
Order By: Relevance
“…Levels of OC remained low between 3 days and 10 days postfracture. In other studies, serum OC levels measured 24 to 48 hours postfracture were reported to decrease, 20 remain unchanged, 21 or increase 22 . Our data showed very little OC activity up to 10 days postfracture.…”
Section: Discussionsupporting
confidence: 46%
“…Levels of OC remained low between 3 days and 10 days postfracture. In other studies, serum OC levels measured 24 to 48 hours postfracture were reported to decrease, 20 remain unchanged, 21 or increase 22 . Our data showed very little OC activity up to 10 days postfracture.…”
Section: Discussionsupporting
confidence: 46%
“…Within a week the osteocalcin level had returned to its initial value and alkaline phosphatase was significantly above its initial value. An increase of the osteocalcin level 1 week after hip fracture has been described by Thompson et al [32] and a continued increase should be expected of the formation variables osteocalcin and alkaline phosphatase as a reaction to the fracture healing. This is in accordance with earlier studies of the osteocalcin [33] and alkaline phosphatase changes after fracture [34][35][36].…”
Section: Discussionmentioning
confidence: 65%
“…[16], who reported a rise after fracture fixation. [16], who reported a rise after fracture fixation.…”
Section: Discussionmentioning
confidence: 99%